ASEAN Regionalism from the Perspective of Global Spatial Politics: A Study on Marine Environmental Protection in Southeast Asian Seas - Dewan An; Wenjiao Xu (International Journal of Asia Pacific Studies, 2026)
ASEAN regionalism is a complex and evolving process shaped by various actors and interactions. While previous studies often framed regionalism as the formation of regional intergovernmental organisations for integration, this study argues for a broader understanding that includes non-state actors, ecological dynamics, and geopolitical contexts. Drawing from critical geography, geopolitics, and area studies, this study proposes a novel analytical framework based on global spatial politics. It redefines regionalism as a spatial ideology and practice of region-construction aimed at controlling natural-social-technical space. This framework gives regions ontological status as actors in international relations and allows for a more nuanced understanding of ASEAN’s role in regional governance. This study examines the historical evolution and multi-dimensional nature of ASEAN regionalism—covering security, economic integration, and environmental cooperation—with a particular focus on marine environmental protection. It highlights how ASEAN’s environmental regionalism is shaped by both political will and the pressure of transboundary ecological issues. By integrating theoretical analysis with empirical observations, this study offers insights into ASEAN’s capacity for spatial governance. This study also contributes to comparative regionalism studies by incorporating environmental dimensions often overlooked in traditional international relations frameworks. Ultimately, it suggests that global spatial politics can help reinterpret the processes of region formation in Southeast Asia beyond institutional and economic paradigms.